Technology transfers within the European defence industry : a transferring firm’s perspective - Routila, Kai (My University, 2026)
Defence expenditures and defence equipment procurement have increased within the EU after the Russian attack on Ukraine in 2022. The European Union has launched many initiatives to support collaboration between member states and to increase joint defence equipment acquisitions. Defence equipment procurements have some special features that make it distinctive from other industries. The customer is a government and that government requests, based on security of supply, that the seller of the defence equipment does cooperation with local firms, including technology transfers to local partners. The customer requests that they have the capability to produce, maintain and operate the acquired defence equipment in all conditions, also during the time of crisis. This thesis examines technology transfers within the European defence industry from a transferring firm’s perspective. The main research question of this thesis is: What is the role of technology transfers to a European defence industry firm? That question is answered by examining why European defence industry firms engage in technology transfers and how does the technology transfer process take place. First, a literature review on technology transfer was conducted during which four technology transfer dimensions were identified: 1) the transfer object, 2) the transfer actors, 3) the transfer mechanisms, and 4) the transfer context. Secondly, those dimensions were used to form interview themes to gain more knowledge. This thesis has a qualitative approach as the purpose is to understand technology transfers as a phenomenon within the defence industry. The empirical part of this thesis consists of semi-structured interviews, with four expert interviewees from a European technology firm that is also active in the defence industry. The results of this thesis show that the role of technology transfers to a European defence firm is to offer the customers what they require by providing them with the possibility for local production, which enhances security of supply and has political value. Technology transfer is a competitive advantage and a means to stand out from the competitors. Previous experience in technology transfer is a significant benefit when negotiating new contracts that involve technology transfer. Having a well-defined process by which technology is transferred is likely to make the transfer more successful. The design of the production and flexibility to transfer to various types of partners at a moderate cost is another benefit. Having a financially stable partner with whom responsibilities and obligations are clear can provide benefits by sharing risks, dispersing production, increasing production capacity and allowing access to the partner’s supply chain.

Puolustusmenot sekä puolustustarvikehankinnat ovat kasvaneet Venäjän hyökättyä Ukrainaan vuonna 2022. Euroopan Unioni on perustanut monia hankkeita, joilla pyritään tukemaan yhteistoimintaa jäsenvaltioiden välillä sekä lisäämään yhteisiä puolustustarvikehankintoja. Puolustustarvikkeiden kaupassa on erityispiirteitä, jotka tekevät siitä erilaisen muihin teollisuudenaloihin nähden. Asiakas on valtio ja kyseinen valtio vaatii huoltovarmuuteen vedoten, että puolustustarvikkeen myyjä tekee yhteistyötä paikallisten yritysten kanssa, muun muassa siirtämällä teknologiaa niille. Asiakas vaatii, että heillä on kyky kaikissa tilanteissa tuottaa, ylläpitää ja käyttää hankittua puolustustarviketta, myös poikkeusolojen aikana. Tämä tutkielma tarkastelee siirtävän yrityksen näkökulmasta teknologiansiirtoja eurooppalaisessa puolustusteollisuudessa. Tutkielman päätutkimuskysymys on: Mikä on teknologian siirtojen merkitys eurooppalaiselle puolustusteknologiayritykselle? Tähän kysymykseen vastataan tarkastelemalla, miksi eurooppalaiset puolustusteollisuusyritykset siirtävät teknologiaa ja miten teknologiansiirtoprosessi on järjestetty. Ensin on kirjallisuuskatsauksessa tunnistettu neljä kategoriaa, joiden perusteella teknologiansiirtoja on tutkittu: 1) siirron kohde, 2) siirron toimijat, 3) siirtomekanismit ja 4) siirron konteksti. Tämän jälkeen, näitä kategorioita on käytetty muodostettaessa haastattelujen teemoja, joilla pyrittiin hankkimaan lisää tietoa. Tässä tutkimuksessa on käytetty laadullista tutkimusotetta, sillä tarkoituksena on lisätä ymmärrystä teknologiansiirroista puolustusteollisuuden ilmiönä. Tutkielman empiirinen osuus toteutettiin tekemällä puolistrukturoituja haastatteluja. Haastatteluihin valittiin neljä asiantuntijaa eurooppalaisesta teknologiayrityksestä, joka toimii myös puolustusteollisuudessa. Tämä tutkimus osoittaa, että teknologiansiirtojen tarkoitus eurooppalaisille puolustusteollisuuden yrityksille on tarjota asiakkaille sitä, mitä he vaativat: mahdollisuutta paikallisvalmistukseen, mikä parantaa huoltovarmuutta ja millä on poliittista merkitystä. Teknologiansiirrot ovat kilpailutekijä ja keino erottautua kilpailijoista. Aiemmat kokemukset teknologiansiirroista on merkittävä etu, kun neuvotellaan uusista sopimuksista, jotka sisältävät teknologiansiirtoja. Kun yrityksellä on hyvin määritelty siirtoprosessi, on siirron onnistuminen todennäköisempää. Kun yritys on suunnittelut tuotantonsa siten, että se kyetään joustavasti ja kohtuullisin kustannuksin siirtämään monelle erityyppiselle kumppanille, on se myös eduksi. Taloudellisesti vakaa kumppani, jonka kanssa on vastuut ja velvollisuudet tarkasti määritelty, mahdollistaa riskien jakamisen, tuotannon hajauttamisen, tuotantokapasiteetin kasvattamisen sekä pääsyn kumppanien toimitusketjuihin.
Keywords: Technology transfer, industrial participation, defence industry, teknologiansiirrot, teollinen yhteistyö, puolustusteollisuus